Structural and optical properties of ZnS/MgNb2O6 heterostructures - Santos, L. P. S.; Cavalcante, L. S.; Fabbro, M. T.; Beltran Mir, H.; Cordoncillo, E.; Andres, J.; Longo, E. [UNESP] (Elsevier B.V., 2015)
In this letter, we report a simple and efficient synthetic procedure where the first step is a coprecipitation/calcination method used to obtain magnesium niobate MgNb2O6 (MN) nanoctystals and in the second stage a microwave assisted hydrothermal method (MAR) is employed to synthesize zinc sulfide (ZnS) nanocrystals and ZnS/MN heterostructures. These heterostructures were characterized by X-ray diffraction (XRD), micro-Raman (MR) spectroscopy, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), high-esolution TEM (HR-TEM), selected area electron diffraction (SAED), energy dispersive X-ray spectrometry (EDX). XRD patterns and MR spectra indicate that MN and ZnS nanocrystals have an orthorhombic and cubic structure, respectively. FE-SEM, TEM and HR-TEM images proved the presence of aggregated MN nanocrystals, ZnS nanocrystals and the presence of ZnS nanocrystals on the surface of MN nanocrystals. Their optical properties were investigated by ultraviolet visible spectroscopy (UV vis) and photoluminescence (PL) measurements at room temperature. ZnS/MN heterostructures show a decrease in the values for the optical band gap with respect to both components. The presence of the ZnS nanocrystals in this heterostructure promotes a high intense PL emission.
Keywords: ZnS/MgNb2O6; Chemical synthesis; Heterostructures; Band gap; Photoluminescence